Research on the Synergy Measurement for Wetland Ecological-Economic-Social Composite System Based on Fractional Order Dynamic System - Zhanyong Jin; Huanhuan Cao; Shuang Xia; Qingyue Liu; Menglin Jia; Rui Wang (Discrete Dynamics in Nature and Society)
For researching the internal structure characteristics and its three subsystems’ evolution of the wetland ecological-economic-social composite system and getting the point that makes wetland ecology, production, and living synergistically develop, in this paper, the coevolution model of wetland complex system based on fractional order dynamic system was established, the genetic algorithm was used to solve the model parameters, and the equilibrium stability of the model was tested by using asymmetric fractional order equilibrium condition. The data of 29 provinces, cities, and districts in China were selected for empirical research, and suggestions for improvement were put forward. The results show that there is a significant nonlinear relationship among the three subsystems, and the stability points exist and change dynamically. This shows that, in practice, only when the local government issues relevant policies, can we achieve the benign coupling and coordinated development of the wetland ecological-economic-social system and achieve the harmonious development of human and nature.